REBT'S APPROACH TO OVERCOMING STUDENTS' ANXIETY IN FOLLOWING THE NATIONAL EXAM - Risda Heldriyana Br Bangun; Netrawati (Literasi Nusantara, 2021)
This article aims to describe a study of the REBT approach in overcoming anxiety. Anxiety can happen to every individual. At last, It will only harm the individual himself. someone who suffers from anxiety will be afraid, not dare to take steps forward, react excessively, have no confidence, have no conviction. Individuals who experience anxiety will continue to think about bad things that have not happened in the future so that they often make the individual locked up in their irrational thoughts, because they focus too much on their anxiety So that in the end the individual will not have any progress , and this will be very detrimental to the individual. Anxiety is triggered by irrational thinking tends to cause emotional disturbances. REBT counseling is a counseling approach that deals with problems related to emotion, cognition, and behavior, by changing the client's irrational and illogical perspective. so that the client can develop himself